Tipologi Pemikiran Islam dalam Falsafah Jawa - Latif, Humayra' Nafisah Mar'atul (Javano Islamicus, 2024)
This study originates from the understanding that the Islamization process in the Indonesian Archipelago, particularly in Java, occurred not only through political or missionary approaches but also through cultural and philosophical engagement. Javanese philosophy became a medium of dialogue between local wisdom and Islamic teachings, especially in the concept of a harmonious relationship between humans and God. The urgency of this research lies in affirming that Islamic thought within Javanese philosophy is not a form of syncretism but an integration of the universal values of Islam with profound local spiritual wisdom. This study employs a qualitative method with a library research approach and integral-descriptive analysis of Javanese philosophical texts and classical Islamic sources. The findings reveal a significant alignment between Javanese theological concepts and Islamic doctrines, such as tan kena kinaya gapa reflecting the Islamic concept of God’s transcendence and absolute power; Gusti Allah orah sare illustrating the divine attribute of constant awareness and vigilance; and sangkan paraning Dumadi parallel to the Islamic view of human creation and ultimate return to God. The novelty of this research lies in demonstrating that Javanese philosophy can be regarded as a localized expression of Islamic spirituality that is both profound and contextually relevant.